2018
DOI: 10.21831/ltr.v17i1.13207
|View full text |Cite
|
Sign up to set email alerts
|

Angela Murray’s Experience of Passing Up as White in Jessie Redmon Fauset’s Plum Bun

Abstract: The aim of this paper is to analyze the experience of Angela Murray, the female mulatto protagonist, when she finally decides to pass as a white person in Plum Bun, a novel written by Jessie Redmon Fauset. Considering that the focus of analysis is a female, the feminist literary criticism is used as the main framework. The contextual method of analysis is supported by some concepts concerning skin color and passing. The result shows that Angela goes through three periods of her existence. At first she plays wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Modesty keeps humanfocused and humble. Forgiveness allows them to be emotionally stable because human does not hold onto anger and resentment (Asmarani, 2018). These attributes will allow them to live their life in a way that reduces stress levels.…”
Section: Moral Values In Human Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Modesty keeps humanfocused and humble. Forgiveness allows them to be emotionally stable because human does not hold onto anger and resentment (Asmarani, 2018). These attributes will allow them to live their life in a way that reduces stress levels.…”
Section: Moral Values In Human Lifementioning
confidence: 99%
“…From the discussion, it can be concluded that courage as one of the moral attribute has several parts of the attribute. It is either observable actions or the cognitions, emotions, motivations, and decisions that bring them about (Asmarani, 2018). Courage also includes physical valor, integrity, perseverance, act willfully, doing what is right (even when one has much to lose), bravery, facing challenge, difficulty, or pain.…”
Section: Courage and Humanity: Attributes Of Moral Values By Petersonmentioning
confidence: 99%